2014
DOI: 10.1007/s12630-014-0194-x
|View full text |Cite
|
Sign up to set email alerts
|

The aging anesthesiologist: a narrative review and suggested strategies

Abstract: PurposeTo address an aging anesthesia workforce, we review the relevant changes and implications associated with age in order to stimulate discussion at the individual, local, and national levels regarding appropriate changes in practice aimed at protecting patient safety.Principal findingsIn a 2013 survey of Canadian Anesthesiologists, 22% were aged 55-64 yr, 7% were aged 65-74 yr, and 3% were older than 74 yr. Clinical abilities decline with age, making older anesthesiologists more likely than their younger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 43 publications
(62 reference statements)
1
32
0
1
Order By: Relevance
“…The authors also offer proposed assessments and possible solutions to ensure patient care is not compromised. 1 This paper reflects broader concerns over a lack of preparedness among professional bodies associated with a range of liberal professions where their members may continue practice into later life without support from formal occupational health services. 2 This is particularly important for medical specialities where there is a heavy reliance on psychomotor skills and rapid responses to emergent situations and where senior specialists are frequently required to attend out of hours to deal with complex clinical cases.…”
Section: To the Editormentioning
confidence: 99%
“…The authors also offer proposed assessments and possible solutions to ensure patient care is not compromised. 1 This paper reflects broader concerns over a lack of preparedness among professional bodies associated with a range of liberal professions where their members may continue practice into later life without support from formal occupational health services. 2 This is particularly important for medical specialities where there is a heavy reliance on psychomotor skills and rapid responses to emergent situations and where senior specialists are frequently required to attend out of hours to deal with complex clinical cases.…”
Section: To the Editormentioning
confidence: 99%
“…When a satisfactory answer to a complex question is not readily available, a common intuitive human response is to find a related question that is easier to answer. In this issue of the Journal, Baxter et al 2 address an important topic that relates to the professionalism of anesthesiologists in dealing with age-related decline in clinical performance. The authors offer a ''proactive'' strategy that hospital departments and practice groups should consider for managing this issue.…”
Section: Kahnemanmentioning
confidence: 99%
“…For example, Campbell et al 5 reported that 52% of patient complaints to the General Medical Council in the United Kingdom (UK) involved anesthesiologists qualified for more than 20 years, whereas only 39% of the cohort were over the age of 45. Baxter et al 2 have asked an important, yet complex, question that requires serious analysis. We cannot, and should not, deny that there may be an unrecognized problem pertaining to some anesthesiologists that is related to an age-related decline in clinical abilities.…”
Section: Kahnemanmentioning
confidence: 99%
See 2 more Smart Citations